Epidural Gas Accumulation in Connection with Canine Degenerative Lumbosacral Disease - Skytte, Ditte; Schmökel, Hugo (Frontiers in Veterinary Science, 2017)
Three dogs were presented with lumbosacral hyperesthesia. Computerized tomography scans were performed in all the cases, and magnetic resonance imaging was performed as well in cases one and three. There was intervertebral disc protrusion causing nerve root compression and epidural gas accumulation in all three cases. The gas-filled cystic structures in cases one and three were within the spinal canal; in case two, the gas was within the disc protrusion. The intervertebral disc vacuum phenomenon is relatively common in dogs, but the formation of an epidural gas accumulation in cases of a lumbar disc protrusion is rare. The clinical significance of these epidural gas accumulations is unknown. Two of the dogs were treated surgically, improved after surgery, and showed no signs of pain in the follow-up examinations.